Pattern of Supply Chain for Manpower Management for Higher Education Sandbox in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research aims to develop the pattern of supply chain for manpower management for higher Education Sandbox in Thailand and evaluation the suitability the pattern. The sample group consisted of ten experts in the field of supply chain and education The research tool was the questionnaire. The data was analyzed using the arithmetic mean, the standard deviation. The research was found that design the pattern of supply chain for manpower management for higher Education Sandbox in Thailand consists of five components namely main suppliers, Manufacture, Customers and consumer The results from ten experts on supply chain and education agreement the pattern of supply chain for manpower management for higher Education Sandbox in Thailand was a high level. It showed that the pattern of supply chain for manpower management for higher Education Sandbox in Thailand can develop manpower.